Cannabis use, dependence and withdrawal in indigenous male inmates. (2nd January 2016) - Rogerson, Bernadette; Jacups, Susan P.; Caltabiano, Nerina
Abstract: Background : No studies have investigated cannabis withdrawal in indigenous or incarcerated populations, and there is currently no standard treatment for cannabis withdrawal in Australian prisons. Aims : This cross sectional survey examines cannabis use, dependence and involuntary (abrupt cessation) withdrawal in incarcerated indigenous males for the purpose of improving clinical management. Methods : 101 consenting inmates (18–40 years) from an Australian correction centre were interviewed. Demographic characteristics, lifetime cannabis use (LCU), severity of dependence, cannabis withdrawal symptoms, psychological well-being and alcohol use were measured and compared using univariate and multivariate analyses. Results : Cannabis withdrawal symptoms were reported in 57% of current cannabis users compared with 16% of non-users ( p  < 0.01), indicating detectable cannabis dependence and withdrawal in a unique indigenous inmate population. Multivariate analysis revealed statistically significant associations between LCU and cannabis dependence (OR = 8.1; 95% CI: 2.2–29.1) when controlling for psychological well-being and alcohol consumption. Conclusions : Upon admission to a correction centre, cannabis users should be assessed and monitored for physical and psychological symptoms of withdrawal. Implications : Routine cannabis withdrawal monitoring will maximise staff and inmate safety. This improvement to policy will ensure appropriate risk management of staff and inmates.